2007
DOI: 10.1021/np068060r
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Phenolic 1-Benzyl-N-methyltetrahydroisoquinolines in Plant Cell Cultures Followed by LC/NMR, LC/MS, and LC/CD

Abstract: (+/-)-1-Benzyl- N-methyltetrahydroisoquinolines 7-10 and 11-14 with one and two hydroxy groups on the aromatic rings, respectively, were fed individually to cultured cells of Corydalis and Macleaya species, respectively. The structures of the metabolites were determined by using combinatorial techniques, including LC/NMR, LC/MS-MS, and LC/CD. The enantiomeric excesses of the metabolites were derived from LC/CD and LC/MS-MS analyses. In cell cultures of Corydalis and Macleaya species, laudanine (7), with a hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…In addition, the 1 H NMR spectrum of 1 also showed signals for three methoxy groups resonating at d H 3.15 (3H, s), 3.81 (3H, s), and 3.83 (3H, s), a N-methyl group at d H 3.21 (3H, s), four aliphatic protons as multiplet resonating at d H 2.92-3.68, as well as three mutual coupling upfield protons as an ABX system resonating at d H 4.46 (1H, dd, J = 9.8, 2.6 Hz), 4.03 (1H, dd, J = 12.4, 2.6 Hz), and 2.85 (1H, dd, J = 12.4, 9.8 Hz). All these indicated that alkaloid 1 possesses a benzylisoquinoline skeleton (Zhou et al, 1991;Cui et al, 2007). The 13 C NMR and DEPT data of 1 showed similarity with those of codamine (Brochmann-Hanssen et al, 1965), except for the characteristic downfield shifts of the carbon resonances at d C 79.6, 62.9, and 54.8 for C-1, C-3, and N-CH 3 , respectively, with respect to those of codamine.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, the 1 H NMR spectrum of 1 also showed signals for three methoxy groups resonating at d H 3.15 (3H, s), 3.81 (3H, s), and 3.83 (3H, s), a N-methyl group at d H 3.21 (3H, s), four aliphatic protons as multiplet resonating at d H 2.92-3.68, as well as three mutual coupling upfield protons as an ABX system resonating at d H 4.46 (1H, dd, J = 9.8, 2.6 Hz), 4.03 (1H, dd, J = 12.4, 2.6 Hz), and 2.85 (1H, dd, J = 12.4, 9.8 Hz). All these indicated that alkaloid 1 possesses a benzylisoquinoline skeleton (Zhou et al, 1991;Cui et al, 2007). The 13 C NMR and DEPT data of 1 showed similarity with those of codamine (Brochmann-Hanssen et al, 1965), except for the characteristic downfield shifts of the carbon resonances at d C 79.6, 62.9, and 54.8 for C-1, C-3, and N-CH 3 , respectively, with respect to those of codamine.…”
Section: Resultsmentioning
confidence: 90%
“…Given that (+)-1S, 2S-laudanidine-N a -oxide and (+)-1S, 2R-laudanidine-N b -oxide hold the similar rotation values (½a 20 D þ 55 for 1S, 2S-laudanidine-N a -oxide and ½a 20 D þ 86 for 1S, 2R-laudanidine-N b -oxide) (Zhang et al, 2012), we could draw a conclusion that the rotation values of this type of benzylisoquinoline alkaloids mainly depend on the chiral center at C-1. From structural and biogenetic point of view, (+)-reticuline (3), also isolated from this plant by us, whose structure and absolute configuration had been determined by a combination of spectroscopic methods (Arbain et al, 1990;Cui et al, 2007;Blanchfield et al, 2003), hold the same chiral center at C-1 with that of alkaloids 1 and 2, and could be considered as model compound for assignment of the absolute configuration by comparison of rotation value, Hence, the absolute configurations at C-1 of alkaloids 1 and 2 were Sconfiguration, identical to that of (+)-reticuline, as determined by their similar specific rotation with 3 (½a 20 D þ 63:9). Another chiral center at N-2 in alkaloids 1 and 2 was determined by the difference in chemical shift for H-8 in 1 and 2, caused by the orientation of the Noxide.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 2D-9D were administered to cell cultures of Corydalis platycarpa and Macleaya cordata (Cui et al, 2007) and the ether-soluble alkaloid fractions (Fig. 2, Fr.…”
Section: Application Of Lc-ms Methods To Chiral Purity Determination mentioning
confidence: 99%
“…It has been demonstrated that (±)-reticuline (6) and (±)-pseudosinomenine (7) were bioconverted to (S)-scoulerine and (S)- tetrahydropalmatrubine (Cui et al, 2007). (±)-Reticuline (6) and (±)-pseudosinomenine (7) may be biotransformed via (S)-laudanine (2) to (S)-tetrahydroprotoberberines.…”
Section: Application Of Lc-ms Methods To Chiral Purity Determination mentioning
confidence: 99%
See 1 more Smart Citation